Making sense of non-binding retail-price recommendations - Stefan Bühler; Dennis L. Gärtner (University of Zurich, Socioeconomic Institute, 2009)
This paper provides a theoretical rationale for non-binding retail price recommendations (RPRs) in vertical supply relations. Analyzing a bilateral manufacturer-retailer relationship with repeated trade, we show that linear relational contracts can implement the surplusmaximizing outcome. If the manufacturer has private information about production costs or consumer demand, RPRs may serve as a communication device from manufacturer to retailer. We characterize the properties of efficient bilateral relational contracts with RPRs and discuss extensions to settings where consumer demand is affected by RPRs, and where there are multiple retailers or competing supply chains.
Keywords: D23; D43; L14; L15; 330; vertical relationships; relational contracts; asymmetric information; price recommendations; Lieferanten-Kunden-Beziehung; Betriebliche Preispolitik; Verhalten in Organisationen; Asymmetrische Information; Unvollkommener Markt; Theorie